UPAYA HUKUM TATA USAHA NEGARA OLEH NOTARIS YANG TIDAK DAPAT MENGAPLIKASIKAN HAK INGKAR NOTARIS AKIBAT PEMERIKSAAN MAJELIS KEHORMATAN NOTARIS YANG TIDAK SESUAI PROSEDUR (STUDI KASUS 13/G/2018/PTUN-TPI) - Pakpahan, Kartina; Fitriyani Pakpahan, Elvira; SIAHAAN, MARSEM PAHAM MARSAOR (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research aims to determine the Notary's responsibility for the deeds they create with the Notary's right of refusal. Additionally, it also examines the legal protection for Notaries who cannot exercise the Notary's right of refusal and analyzes the legal efforts made by Notaries in the context of Administrative Court proceedings. This research is normative in nature, using a Legislative Approach and a Case Approach in legal analysis. The legal sources involved in this research include primary and secondary legal materials. Based on the research findings, notaries have three responsibilities in carrying out their duties: civil, criminal, and administrative. Protection for Notaries who cannot exercise their right to refuse requires Notaries to disclose the contents of the deed and provide testimony in court. In the trial, it is known that the Notary Honorary Council (MKNW) can accompany the Notary during the examination process in front of the Investigator, Public Prosecutor, or Judge. What is meant by "accompanying" in this context means being present, while the word "may" in a regulation reflects the discretion of an MKN institution. The legal efforts undertaken by the Notary in the State Administrative Court in Decision Number: 13/G/2018/PTUN-TPI are not in accordance with Article 66 paragraph 1 of the Notary Public Law (UUJN) and the Regulation of the Minister of Law and Human Rights Number 7 of 2016 concerning the Honorary Council of Notaries in Article 23. In this case, there is a violation of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 7 of 2016 concerning the Honorary Council of Notaries. The Deputy Chairperson of the Regional Honorary Council of the Riau Islands Province was not granted the authority to form an Examination Board in the examination of the Plaintiff as a Notary; therefore, the approval must be declared invalid so that the Notary cannot file a lawsuit with the Administrative Court to obtain legal justice and maintain the legal force of the deed and the procedure for making the deed.